Phương trình tích

Võ Nguyễn Anh Thư

\(2x^2+3x+1=0\)

\(\left(x^2+1\right)\left(x-1\right)=0\)

Nguyễn Việt Hoàng
29 tháng 6 2020 lúc 21:37

2x2 + 3x + 1 = 0

\(\Rightarrow\) 2x2 + 2x + x + 1 = 0

\(\Rightarrow\) 2x ( x + 1 ) + ( x + 1 ) = 0

\(\Rightarrow\) ( x + 1 )( 2x + 1 ) = 0

\(\Rightarrow\left[{}\begin{matrix}x+1=0\\2x+1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=-1\\x=-\frac{1}{2}\end{matrix}\right.\)

\(\Rightarrow\) \(S=\left\{-1;-\frac{1}{2}\right\}\)

( x2 + 1 )( x - 1 ) = 0

Mà x2 + 1 > 0

=> x - 1 = 0

=> x = 1

Bình luận (0)

Các câu hỏi tương tự

Khoá học trên OLM của Đại học Sư phạm HN

Loading...

Khoá học trên OLM của Đại học Sư phạm HN